(untitled) (Economics and region, 2023)
The market environment and the financial and economic crisis caused by the martial law in Ukraine creates new challenges for state bodies and enterprises and requires the improvement of technologies for combating fraud and financial violations and the use of the institute of forensic accounting. The rapid development of forensic accounting as a field of knowledge and a type of professional activity in the world and in Ukraine is evidenced by the sharp growth of international specialized firms engaged in forensic accounting research and the active introduction of the discipline "forensic accounting" into the educational process of leading institutions of higher education economically developed countries of the world. The article examines the theoretical and methodological foundations of forensic accounting, namely the essence, objects, sources, functions and features of development in Ukraine and other countries of the world. Today there is no legally established definition of forensic accounting in Ukraine. Among scientists, there are 6 approaches to defining this concept: procedural form; research of financial and economic activity and accounting data of the enterprise; the process of using special knowledge in accounting; research by an expert in the field of economics and accounting of material objects, processes; procedural research of economic objects and processes. On the basis of the study of the opinions of scientists, a proper interpretation of the term "forensic accounting " is proposed. It has been established that educational institutions pay insufficient attention to forensic accounting, to the conclusion of education in developed countries of the world. Of the 20 analyzed University, only 45% have it as a component of education in the electoral cycle of the discipline of a professional direction, which is insufficient to increase the level of professionalization in this area in view of the new challenges of the external environment.The expediency of introducing a mandatory educational discipline "Forensic accounting" in the training of accounting and taxation specialists and approving a specialized professional standard, based on the example of Australia, is substantiated.